Compatibility for Marriage in Islam (Kufū) and Societal Perspectives - Sana Binte Haroon; Dr Shahzadi Pakeeza (jihat-ul-islam, 2022)
This research explores subject associated to compatibility of spouses in a marital contract in present-day Muslim marriages. It includes social compatibility i.e., the concept of kufu or equality between the spouses under the teaching of Islam. This research highlights the provisions in Quran and Sunnah for a compatible partner for marriage and also discussed about the contemporary Pakistani society norms and cultural barriers that overlooks the Shariah provisions for Kufū . The research finds out that in the matter of marriages the role of family and society is also very important for deciding the perfect match. The main focus of this study was to know about the views of youth about these concepts of social compatibility and the role of wali. It is qualitative research using descriptive and analytical research approach. Content analysis was the method for analyzing the data. The study concludes that despite societal pressures and norms, the rulings and conditions of Shariah should also be taken into account, as they form the basis of a sound marriage.